The Urgency of Ecological Education in Harmonizing Citizens' Rights and Obligations in Urban Waste Management - Salsabila Wildan Hakim; Qisthi Adheani Ziyad; Suparmi (Aslim: Journal of Education and Islamic Studies, 2026)
Urban waste management in Indonesia is facing considerable challenges due to the increasing volume of waste and inadequate infrastructure, making it difficult to fulfill the community's right to a clean and healthy environment. The purpose of this study is to assess the community's ecological knowledge and values in the context of community development. This study used a systematic literature review method by searching for articles based on the “Publish or Perish” principle, using keywords such as “urban waste management” and “ecological citizenship.” From the initial 100 articles, 22 articles were selected for analysis. The results of this study show that there is a relationship between rights and obligations that are mutually supportive, but often unbalanced. Low community participation and weak law enforcement in Indonesia disrupt the overall performance of the system. On the other hand, a mixed management model that combines community efforts with government assistance has been proven to increase involvement and efficiency in waste management. The study concludes that a more in- depth approach is needed through strengthening regulations, public education, and cooperation between multiple parties in order to achieve a healthy and clean urban environment.